2017
DOI: 10.3892/etm.2017.4234
|View full text |Cite
|
Sign up to set email alerts
|

Significance of new blood vessels in the pathogenesis of temporomandibular joint osteoarthritis

Abstract: We studied the significance of new blood vessels in the pathogenesis of temporomandibular joint osteoarthritis (TMJOA). Fifteen 8-week-old female Sprague-Dawley rats were selected to establish TMJOA models of gradually induced occlusal disorders. Five rats were sacrificed at 4, 8 and 16 weeks, and histological exam was conducted along with micro-computed tomography observation on the condyle specimen. The distribution and number of new blood vessels breaking were observed through the tidemark through CD34 immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
2
7
0
1
Order By: Relevance
“…With respect to these features, angiogenesis within the TMJ disc has been shown as internal derangement develops 11 . Our histopathological analysis demonstrated vascular infiltration in every disc with varying degrees, and this is in line with the results from Yoshida et al 22 An animal study by Liu et al 23 indicated changes in articular cartilage matrix under excessive loading as an essential factor for the invasion of blood vessels. Tissue fragmentation was also frequently noted in our degenerated discs’ sample.…”
Section: Discussionsupporting
confidence: 92%
“…With respect to these features, angiogenesis within the TMJ disc has been shown as internal derangement develops 11 . Our histopathological analysis demonstrated vascular infiltration in every disc with varying degrees, and this is in line with the results from Yoshida et al 22 An animal study by Liu et al 23 indicated changes in articular cartilage matrix under excessive loading as an essential factor for the invasion of blood vessels. Tissue fragmentation was also frequently noted in our degenerated discs’ sample.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, the significance of Chm-1 expression associated with angiogenesis during the pathogenesis of temporomandibular joint (TMJ) osteoarthritis was investigated [38]. Chm-1 protein expression was observed in the proliferative and hypertrophic zone of mandibular condylar cartilage, and chondrocyte-like cells in the TMJ disc by immunohistochemistry analyses; which is indicative of a role of Chm-1 in the regulation of TMJ remodelling via preventing blood vessel invasion of the condylar cartilage and by maintaining the integrity of the condylar cartilage and TMJ disc [28].…”
Section: The Effect Of Chm-1 In Cartilage and Osteoarthritis (Oa) Promentioning
confidence: 99%
“…Three steps were followed to perform enrichment analysis of DEGs, which revealed that DEGs mainly enriched in vasculature development, response to growth factor, positive regulation of cell migration, and ECM-receptor interaction. Many studies found that vasculature development at the osteochondral junction and synovium was associated with the onset and development of OA [29, 30]. Meanwhile, some growth factors, such as VEGF and NGF, were obviously upregulated in subchondral spaces, vascular channels and chondrocytes of OA patients [31].…”
Section: Discussionmentioning
confidence: 99%